2017
DOI: 10.1002/jsfa.8688
|View full text |Cite
|
Sign up to set email alerts
|

Fortified tuna bone powder supplementation increases bone mineral density of lactating rats and their offspring

Abstract: Calcium supplement from tuna bone powder was effective in preventing maternal osteopenia. Tuna bone, which is a readily available fishing industrial waste, is a good alternative source of calcium supplement that increases BMD in both lactating mothers and the neonates. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…Fish bones are rich in calcium with high bioavailability (Malde et al, ). Therefore, some researchers have focused on the utilization of calcium in fish bones (Nawaz et al, ; Suntornsaratoon, Charoenphandhu, & Krishnamra, ). Despite the increasing efforts to obtain new products from this waste, the majority are still thrown away or used as animal food (Alkaya & Demirer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fish bones are rich in calcium with high bioavailability (Malde et al, ). Therefore, some researchers have focused on the utilization of calcium in fish bones (Nawaz et al, ; Suntornsaratoon, Charoenphandhu, & Krishnamra, ). Despite the increasing efforts to obtain new products from this waste, the majority are still thrown away or used as animal food (Alkaya & Demirer, ).…”
Section: Introductionmentioning
confidence: 99%
“…18 , 31 By contrast, calcium supplementation does not enhance the trabecular bone structure in lactating rats. 32 Surprisingly, annatto tocotrienol did not act synergistically with calcium carbonate in this study to further enhance its effects on bone microstructure. A previous report indicated that annatto tocotrienol prevents the deterioration of bone microstructure in animal models of bone loss induced by testosterone deficiency, 18 , 19 , 31 oestrogen deficiency 33 and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 52%
“…Similarly, calcium supplementation of the rat dams does not improve bone strength of pups. 32 This observation contradicted the findings of Mohamad et al (2018) that calcium in drinking water improves the femoral load and Young’s modulus of rats with testosterone deficiency induced by buserelin. 18 Annatto tocotrienol also improves the bone strength of the rats in some models of osteoporosis 17 , 18 but is ineffective in this case.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Malde et al (2010) later conducted a double-blind randomized crossover trial and found that calcium from enzyme-treated salmon and cod bones was well absorbed by healthy young men. Besides, it was also reported that fortified tuna bone powder supplementation increased bone mineral density and improved the maternal bone microstructure of lactating rats and their offsprings (Suntornsaratoon et al, 2018). Therefore, it is possible to provide a novel nutraceutical with high bioavailability for Ca and Ca-fortified food supplements, such as fruit juice or Ca-rich foods, and as alternatives to dairy products (Jung et al, 2006;Nemati et al, 2016).…”
Section: Application Of Fish Bone Minerals In Functional Food/nutracementioning
confidence: 99%